The mediating role of sexual arousal and gratification in the relationship between online pornography motivation and tendencies towards internet-pornography-viewing disorder (IPD) - Ma’rof, Aini Azeqa; Abdullah, Haslinda; Dahamat Azam, Mohamad Naqiuddin (Human Resources Management Academic Research Society, 2024)
This study explores the mediating roles of sexual arousal and gratification in the relationship between online pornography motivation and tendencies towards internet-pornography viewing disorder (IPD) among young adults who reported watching pornography. Utilizing a cross-sectional survey of 405 participants, data were collected through online questionnaires distributed via pornography-related groups and websites. The results indicate that online pornography motivation significantly predicts tendencies towards IPD, with sexual arousal and gratification serving as crucial mediators. Young adults with higher motivations to view online pornography experience greater sexual arousal and gratification, which in turn increase tendencies towards problematic use. This highlights the importance of addressing motivations for pornography use and the reinforcing effects of sexual arousal and gratification in interventions aimed at reducing IPD. Practical strategies suggested include implementing cognitive-behavioral therapy (CBT), psychoeducational programs, and mindfulness-based interventions such as Mindfulness-Based Stress Reduction (MBSR). In conclusion, the study provides empirical evidence on the mediating roles of sexual arousal and gratification in the relationship between online pornography motivation and tendencies towards IPD. By understanding these dynamics, mental health professionals can develop targeted strategies to support young adults in managing problematic pornography use, ultimately improving their overall wellbeing. These findings offer valuable insights for both academics and practitioners in mental health and behavioral intervention.